Quasi‐Biweekly Mode of the Asian Summer Monsoon Revealed in Bay of Bengal Surface Observations. Issue 12 (3rd December 2020) - Sree Lekha, J.; Lucas, Andrew J.; Sukhatme, Jai; Joseph, Jossia K.; Ravichandran, M.; Suresh Kumar, N.; Farrar, J. Thomas; Sengupta, D.
Abstract: Asian summer monsoon has a planetary‐scale, westward propagating "quasi‐biweekly" mode of variability with a 10–25 day period. Six years of moored observations at 18°N, 89.5°E in the north Bay of Bengal (BoB) reveal distinct quasi‐biweekly variability in sea surface salinity (SSS) during summer and autumn, with peak‐to‐peak amplitude of 3–8 psu. This large‐amplitude SSS variability is not due to variations of surface freshwater flux or river runoff. We show from the moored data, satellite SSS, and reanalyses that surface winds associated with the quasi‐biweekly monsoon mode and embedded weather‐scale systems, drive SSS and coastal sea level variability in 2015 summer monsoon. When winds are calm, geostrophic currents associated with mesoscale ocean eddies transport Ganga‐Brahmaputra‐Meghna river water southward to the mooring, salinity falls, and the ocean mixed layer shallows to 1–10 m. During active (cloudy, windy) spells of quasi‐biweekly monsoon mode, directly wind‐forced surface currents carry river water away to the east and north, leading to increased salinity at the moorings, and rise of sea level by 0.1–0.5 m along the eastern and northern boundary of the bay. During July–August 2015, a shallow pool of low‐salinity river water lies in the northeastern bay. The amplitude of a 20‐day oscillation of sea surface temperature (SST) is two times larger within the fresh pool than in the saltier ocean to the west, although surface heat flux is nearly identical in the two regions. This is direct evidence that spatial‐temporal variations of BoB salinity influences sub‐seasonal SST variations, and possibly SST‐mediated monsoon air‐sea interaction. Plain Language Summary: The north Bay of Bengal (BoB) is characterized by 1–10 m deep layer of river water, very stable density stratification, and deep isothermal layer warmed by penetration of sunlight below the thin mixed layer. Thermodynamic structure of the upper ocean influences intraseasonal active‐break cycles of the summer monsoon and promotes intensification of postmonsoon tropical cyclones by inhibiting storm‐induced cooling of sea surface temperature. Hence, it is important to understand the space‐time variability of surface salinity in this basin. The quasi‐biweekly (10–25 day) oscillation is a prominent mode of the Asian summer monsoon, seen in winds, cloudiness, rainfall and surface heat flux. Six years of mooring observations at 18°N in the north BoB show large amplitude (2–8 psu) changes in surface salinity on quasi‐biweekly timescales in summer and autumn. Using moored observations, satellite data and reanalyses, we show that changes in surface winds associated with quasi‐biweekly monsoon mode and its embedded low‐pressure systems drive large changes in surface salinity and coastal sea level. We show that the response of SST to subseasonal variations of surface heat flux is enhanced in the presence of a thin layer of river water. These observations have important implications for regional air‐sea interaction on subseasonal timescales. Key Points: Moored observations show large amplitude quasi‐biweekly variability of surface salinity in the north Bay of Bengal Mesoscale eddies and shallow wind‐driven monsoon currents lead to lateral dispersal of river water Shallow, fresh layer enhances sea surface temperature response to surface heat flux on subseasonal timescales